Pertanian Bioindustri Berbasis Zero Waste melalui Pemanfaatan Biogas untuk meningkatkan Nilai Tambah Agribisnis dan Keberlanjutan - Roosganda Elizabeth (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
Zero-waste-based bioindustrial agriculture is an agricultural development approach that integrates crop and livestock subsectors through the optimal utilization of agricultural waste to generate economic, social, and environmental benefits. This study aims to analyze the role of biogas utilization within a zero-waste bioindustrial agriculture system and its contribution to value-added creation and agribusiness sustainability. The study employed a qualitative descriptive approach supported by quantitative analysis of economic and financial feasibility data related to biogas utilization. Data were collected from previous studies, scientific literature, and other relevant sources. The results indicate that the conversion of livestock waste into biogas provides economic benefits through additional income generation, energy cost savings, and the utilization of biogas slurry as organic fertilizer. Financial feasibility analysis demonstrates that biogas enterprises are economically viable, as indicated by a Benefit-Cost Ratio (B/C Ratio) greater than one and an Internal Rate of Return (IRR) exceeding the prevailing interest rate used in the analysis. Beyond direct economic benefits, the bioindustrial system also creates opportunities for agribusiness MSME development through the production of organic fertilizers, compost, liquid organic fertilizers, and rural energy enterprises. Crop–livestock integration within the bioindustrial framework promotes a circular economy that enhances resource-use efficiency, value-added creation, and agribusiness sustainability. Therefore, the development of zero-waste-based bioindustrial agriculture should be promoted as a strategic approach to improving farmers’ welfare while supporting environmental sustainability.